Antimutagenicity and induction of antioxidant defense by flavonoid rich extract of Myrcia bella Cambess. in normal and tumor gastric cells - Serpeloni, Juliana Mara [UNESP]; Leal Specian, Ana Flávia; Ribeiro, Diego Luis; Tuttis, Katiuska; Vilegas, Wagner [UNESP]; Martínez-López, Wilner; Dokkedal, Anne Lígia [UNESP]; Saldanha, Luiz Leonardo [UNESP]; De Syllos Cólus, Ilce Mara; Varanda, Eliana Aparecida [UNESP] (Elsevier, 2015)
Ethnopharmacological relevance The Brazilian Cerrado is an important source of natural products, such as Myrcia bella Cambess (MB, also known as mercurinho). MB leaves are popularly used for the treatment of diabetes and gastrointestinal disorders; however, only its hypoglycemic activity has been experimentally described. Aim of the study Because MB is used to treat gastrointestinal disorders, the present study characterized biological activities of hydroalcoholic MB extract in human normal and tumor gastric cells. Materials and methods Cytotoxic, antiproliferative, genotoxic and protective effects were evaluated, as well as the effects of the MB extract on gene expression. Results The MB extract induced cytotoxicity in tumor cells at lower concentrations compared with normal cells as assessed by the MTT assay. Moreover, the MB extract induced necrosis based on acridine orange/ethidium bromide staining. An antiproliferative effect was evidenced through an arrest in the G2/M phase detected by flow cytometry and a decrease in the nuclear division index using the cytokinesis-block micronucleus cytome assay. Cells treated with MB extract combined with doxorubicin (DXR) showed increased NUBDs, which may be related to the gene amplification of CCND1. Antimutagenic effects were also observed and may be associated with the antioxidant activities detected using the CM-H2DCFDA probe. Conclusions Our findings showed the following: (a) high concentrations of MB induced cytotoxicity and cell death by necrosis; (b) its antiproliferative effect was associated with G2/M arrest; and (c) its antioxidant activity could be responsible for the observed antimutagenic effects and for protective effects against gastrointestinal disorders previously described to MB. Although these effects are not specific to normal or tumor cells, they provide a panel of biological activities for further exploration.
Keywords: Antioxidant; Antiproliferative; Gastric disorders; Mutagenicity; Myrcia bella; Necrosis